Analisis Kemampuan Pembuktian Matematis Mahasiswa Menggunakan Pendekatan Induktif-Deduktif Pada Mata Kuliah Analisis Real - Karunia Eka Lestari (Universitas Mathla'ul Anwar Banten, 2015)
This study presents about research results using quantitative descriptive approach and experiment research mothod with pre-experimental design: the one-shot case study design conducted at semester VI student in 2014-2015 academic years at real analysis course. The purpose ofthis study is to describe the data on the ability of the student mathematical proofs using inductive-deductive approach, get a picture of the problems faced by students and examine the interventions required students to overcome the problems encountered in doing mathematical proofs. Based on the analysis data gained research results shows that: 1) at trust level 95%, there is not enought proofs to state that mathematical proofs ability of student using inductive-deductive approach at real analysis course is over 81% of assigned ideal criteria; 2) the problems faced by student in doing mathematical proofs namely problems in reading and understanding of mathematical proofs, showing correctness proof of a statement mathematically, doing proofs directly and indirectly or with mathematical induction and developing mathematical arguments to prove or decline a statement. And 3) the interventions need to be given to student overcoming the problems, namely by giving reinforcement towards material mastery of prerequisite, doing conditioning through drill, practice, and exercise, giving scaffolding with deductively proofs instruction by stating definition or theorem to conduct mathematical proofs.